Interconnections among rural practices and Food-Water-Energy Security Nexus in the Atlantic Forest biome - Duarte, Gabriela Teixeira (2021)
Global agricultural production is expected to double by 2050 due to both global population increase and changes in diets as a consequence of growing incomes. This also means more pressure on water resources, as agriculture accounts for 70 % of global water withdrawal and for energy production as the entire food supply chain accounts for about 30 % of total global energy consumption. Although there are ongoing discussions related to the sustainability of food, water, and energy sectors, integrating these sectors is still rare and challenging. We investigated the effects of agricultural practices on the Food, Water and Energy (F-W-E) nexus security systems by evaluating the results reported in scientific literature. Focusing on the Brazilian Atlantic Forest biome as a study case, our main goals were 1) to elucidate the impacts of rural conservation practices on food, water, and energy production based on literature analysis, 2) to propose F-W-E attributes and evaluate how they are addressed by rural practices. Our findings demonstrated, in general, a positive impact of agricultural conservation practices on F-W-E security attributes. Indeed, 76 % of the combination between a conservational practice with a F-W-E attribute was positive. Some agricultural practices, such as no tillage are very well documented (45 % of all combinations), especially regarding their effects on soil quality parameters. We found few results connecting agricultural practice and energy aspects. These results are key elements that corroborate with the agriculture multifunctionality approach, and the results can better guide the planning of strategies in the agricultural sector and subsidize decision making.